The NAIRU determinants: What’s structural about unemployment in Europe? - Heimberger, Philipp (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2017)
This paper analyzes the determinants of the European Commission’s estimates of the non-accelerating inflation rate of unemployment (NAIRU) for 14 European countries during 1985–2012. The NAIRU is a poor proxy for ‘structural unemployment’. Labor market institutions – employment protection legislation, union density, tax wedge, minimum wages – underperform in explaining the NAIRU, while cyclical variables – capital accumulation and boom-bust patterns in housing markets – play an important role. This finding is policy-relevant since the NAIRU is used to compute potential output and structural budget balances and, hence, has a direct impact on scope and evaluation of fiscal policies in Europe.